2018
DOI: 10.14814/phy2.13750
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of spatio-temporal convergent properties in central vestibular neurons in monkeys

Abstract: The spatio‐temporal convergent (STC) response occurs in central vestibular cells when dynamic and static inputs are activated. The functional significance of STC behavior is not fully understood. Whether STC is a property of some specific central vestibular neurons, or whether it is a response that can be induced in any neuron at some frequencies is unknown. It is also unknown how the change in orientation of otolith polarization vector (orientation adaptation) affects STC behavior. A new complex model, that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(259 reference statements)
0
1
0
Order By: Relevance
“…We recently demonstrated that cross-coupling from horizontal to vertical and roll components of VOR were also coded by canal-otolith convergent VO neurons ( Yakushin et al, 2017 ). Polarization vectors of VO neurons are flexible and tend to align their orientation with gravity ( Eron et al, 2008a , 2018 ), even when animals were in complete darkness without any specific training stimulus. This is distinct from polarization vectors coded by Eye-Head-Velocity (EHV) and Position-Vestibular-Pause (PVP) neurons that project to oculomotor neurons and therefore are part of the direct VOR pathway ( Kolesnikova et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that cross-coupling from horizontal to vertical and roll components of VOR were also coded by canal-otolith convergent VO neurons ( Yakushin et al, 2017 ). Polarization vectors of VO neurons are flexible and tend to align their orientation with gravity ( Eron et al, 2008a , 2018 ), even when animals were in complete darkness without any specific training stimulus. This is distinct from polarization vectors coded by Eye-Head-Velocity (EHV) and Position-Vestibular-Pause (PVP) neurons that project to oculomotor neurons and therefore are part of the direct VOR pathway ( Kolesnikova et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%